Nördliches Eismeer, Barents See / herausgegeben vom Reichs-Marine-Amt, 1901 - Germany. Reichs-Marine-Amt (Berlin : Reichs-Marine-Amt, 1926)
Kleine Berichtigungen: . 1926 Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Nr. 155 (Tit. XIII Nr. 31)."; Includes abbreviation table and 3 inset maps.; Annotated in pencil Grayscale; 1:2,000,000